Profit Optimization of Sambal SohibKoe Using Linear Programming Simplex Method - Charles Nicole; Christopher Vergara Lidaya; Dudy Effendy; Feby Lia; Felix Kharisma; Khefen; Meilisa Permata Wonowijaya (International Journal of Managemen Analytics (IJMA), 2023)
Mrs. Devi's Sambal business named "SohibKoe" is one of the businesses in the culinary field which is growing rapidly in Indonesia or what is commonly called Micro, Small and Medium Enterprises (UMKM). In this business, the problems faced are the price and limitations of raw materials and the number of customers also affect the increase in profits which makes Sambal run out quickly with an uncertain time which makes the profit earned not maximized. This research was conducted with the aim of formulating problem-solving in profit optimization in Micro, Small and Medium Enterprises (MSMEs) from Mrs. Devi's Sambal SohibKoe business. The simplex method is a way to solve linear programming problems where a repetition of mathematical procedures is carried out to test corner points so that an optimal solution is found. The data used in the research conducted is data obtained directly from interviews with Mrs. Devi as a seller of SohibKoe chili sauce. Based on research through the simplex method linear program, the results of optimization calculations obtained include stating that the maximum profit per week is 155,000 with a production amount of 8 bottles of sambal cumi petai and 7 bottles of Sambal Teri